Addition of PSMA ADC to enzalutamide therapy significantly improves survival in in vivo model of castration resistant prostate cancer. Issue 3 (20th November 2015) - DiPippo, Vincent A.; Nguyen, Holly M.; Brown, Lisha G.; Olson, William C.; Vessella, Robert L.; Corey, Eva
Abstract : BACKGROUND: Despite multiple new therapies available to patients with advanced castration‐resistant prostate cancer (CRPC), the overall survival benefit still remains relatively short. Therefore, it is important to investigate additional treatment options that could achieve greater efficacy. Because of tumor heterogeneity and the development of resistance to treatment with single agents, combination therapies using existing drugs with new agents can potentially broaden individual therapeutic windows and achieve improved efficacy and safety profiles. The objective of the current studies was to evaluate the efficacy of combination of enzalutamide (ENZ) with prostate specific membrane antigen antibody drug conjugate (PSMA ADC) to inhibit CRPC patient‐derived xenografts (PDX) in a preclinical setting. METHODS: Subcutaneous LuCaP 96CR prostate cancer PDX bearing mice were treated with a single dose of PSMA ADC (2.0 mg/kg) or 5 days a week ENZ (50 mg/kg) as monotherapy or with a combination of these two agents. The effects of the PSMA ADC+ENZ combination were compared to PSMA ADC alone, ENZ alone, and placebo control. IHC analyses were performed to determine PSMA, AR, ARV7, and GR expression and effects on proliferation. RESULTS: All treatments inhibited tumor progression but with different efficacy. At 6 weeks, in the control and ENZ groups all tumors were progressing, while in the PSMA ADC group only 5/11 were progressing, two remained unchanged and four tumors had decreased tumor volume. Moreover, all animals in the PSMA ADC+ENZ group had smaller tumors at week 6 when compared to their size at enrollment (week 0). A 14‐week followup showed that all three treatments resulted in significant survival benefits but the combination effects were the most pronounced resulting in PSMA ADC+ENZ versus ENZ HR = 0.093 ( P = 0.0045) and PSMA ADC+ENZ versus PSMA ADC HR = 0.051 ( P = <0.0001) with no deaths observed in the combination group. CONCLUSIONS: Our results clearly indicate that the combination of PSMA ADC+ENZ possesses strong antitumor activity and significantly improves survival over ENZ monotherapy using the LuCaP 96CR PDX model. These results provide a strong rationale for clinical testing of PSMA ADC in combination with ENZ and/or other androgen‐directed treatment strategies. Prostate 76:325–334, 2016 . © 2015 Wiley Periodicals, Inc.